Effects of Using COVID-19 Medication Protocol on Medication Error and the Results of Using Telepharmacy System for Counseling and Adverse Drug Event Monitoring in Phraphutthabat Hospital - จันพลา เกศกนก (Journal of Health Science of Thailand, 2023)
Initially, the system of prescribing medication to treat COVID-19 in Phraphutthabat hospital, including favipiravir, remdesivir and molnupiravir. was lack of clear prescription protocol and lack of patient monitoring after the prescription. Thus, the reported incidents of prescribing errors were as high as 4.13 times per 1,000 prescriptions and dispensing errors were 0.65 times per 1,000 prescriptions, two of which were at the D severity level, an error occurred that reached the patient. Such incidents, although unharmed, necessitated close monitoring. The purpose of this study was to investigate the effects of using COVID-19 medication protocol on medication errors and the results of using telepharmacy system for counseling and adverse drug events monitoring. This was a retrospective study conducted between 1st April and 25th June 2022. Data were analysed by descriptive statistics, Chi-squared test and Fisher’s exact test. Of the total 2,569 prescriptions the findings show that the medication errors significantly decreased from 4.90 to 1.55 times per 1,000 prescriptions (p<0.05). The prescribing errors were reduced from 4.13 to 1.55 times per 1,000 prescriptions with the B severity level, an error occurred but the medication did not affect the patient; while the dispensing error was reduced from 0.65 to 0 times per 1,000 prescriptions, respectively, compared with the revised pre-protocol incidence data. After, using COVID-19 medication protocol, 1 patient was reported diarrhea (0.04%) from molnupiravir, 6 patients reported dizziness from molnupiravir (0.23%), and 2 patients reported nausea/vomiting from favipiravir (0.07%) with mild adverse events severity level. The patient’s satisfaction score was at high level 77.75% (N=956, mean=3.89/5, S.D.=0.63). Therefore, using COVID-19 medication protocol helped reducing medication errors and the information technology system used to follow up with patients could monitor adverse drug events. Such data can be applied for patient counseling in the future so that they will be satisfied after receiving the service.